Remuneration motivation discipline and job satisfaction on the performance of education staff at the faculty of mathematics and natural sciences Sebelas Maret University - Wiji Utama; Sarsono Sarsono; Ida Aryati Diyah Purnomo Wulan (Enrichment : Journal of Management, 2023)
The performance of Sebelas Maret University educational staff is needed to facilitate activities on and off campus. This study aims to determine the effect of remuneration, work motivation, work discipline, and employee satisfaction on employee performance at the Faculty of Mathematics and Natural Sciences, Sebelas Maret University. This research method uses a quantitative descriptive approach. The population in the study was 51 staff members of the Faculty of Mathematics and Natural Sciences, Sebelas Maret University, all of whom were taken as research samples using a total sampling technique. Data collection using a questionnaire. The data analysis technique used statistical analysis, namely multiple linear regression test, F test, t-test, and coefficient of determination. The results showed that remuneration, work motivation, work discipline, and employee satisfaction have a positive and significant effect on employee performance at the Faculty of Mathematics and Natural Sciences, Sebelas Maret University.